Junior doctors and conscientious objection to voluntary assisted dying: ethical complexity in practice - McDougall, Rosalind J. (Journal of medical ethics, 2022)
In jurisdictions where voluntary assisted dying (VAD) is legal, eligibility assessments, prescription and administration of a VAD substance are commonly performed by senior doctors. Junior doctors’ involvement is limited to a range of more peripheral aspects of patient care relating to VAD. In the Australian state of Victoria, where VAD has been legal since June 2019, all health professionals have a right under the legislation to conscientiously object to involvement in the VAD process, including provision of information about VAD. While this protection appears categorical and straightforward, conscientious objection to VAD-related care is ethically complex for junior doctors for reasons that are specific to this group of clinicians. For junior doctors wishing to exercise a conscientious objection to VAD, their dependence on their senior colleagues for career progression creates unique risks and burdens. In a context where senior colleagues are supportive of VAD, the junior doctor’s subordinate position in the medical hierarchy exposes them to potential significant harms: compromising their moral integrity by participating, or compromising their career progression by objecting. In jurisdictions intending to provide all health professionals with meaningful conscientious objection protection in relation to VAD, strong specific support for junior doctors is needed through local institutional policies and culture.